Une introduction aux communs de la connaissance - Hervé LE CROSNIER (Tic & Société)
We propose an introduction to the knowledge commons based on an attempt to define the commons themselves, and then evaluate how they are related to the intangible fields of knowledge and the digital. It seems difficult to settle on a canonical definition of the commons. Despite a rapidly growing scientific corpus, there are still different approaches according to countries, regions, cultures... But this is certainly a benefit : the commons are above all the result of lived experience. The article presents different approaches to the commons, both in theoretical debates and in the practices of movements associated with resource sharing. It documents the shift from theory mainly concerned with localized resources to cooperative practices expanded through digital technology.